Nanomaterials for Dye Sensitive Solar Cells: A Literature Review - RAHEEM, SK ABDUL; Reddy, K.Chandra Sekhar (International Journal of Psychosocial Rehabilitation, 2020)
In this work, the progress in nanomaterials for dye-sensitized solar cells is surveyed. The survey shows that the majority of exploratory investigations are focused on the role of dye-sensitized solar cells in changeable nanomaterials. The photoelectrochemical system's favourable impact These exploratory research, in reality, have certain methodological concerns. According to these investigations, the literature has consistently generated contradictory results, and no one has come to a conclusion about the phenomenon's reality.